2012
DOI: 10.1080/21672857.2012.11519696
|View full text |Cite
|
Sign up to set email alerts
|

The GEM Theory of the Unification of Gravitation and Electro-Magnetism

Abstract: The GEM (Gravity Electro-Magnetism), theory is presented as an alloy of Sakharov and Kaluza-Klein approaches to field unification. GEM uses the concept ofgravity fields as Poynting fields to postulate that the non-metric portion of the EM stress tensor becomes the metric tensor in strong fields leading to "self-censorship". Covariant formulation of the GEM theory is accomplished through definition of the spacetime metric tensor as a portion of the EM stress tensor normalized by its own trace: g ab = 4 (F c a F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 7 publications
0
5
0
Order By: Relevance
“…The generation of the solitons relies on a 7D, but essentially 5D, space time matter induction and scattering from an embedded 7D flat or Einsteinian space [18,22,73,143]. These models are also inspired from non-multi-fold theories [19][20][21][23][24][25]. Handling of chiral fermions, absent in odd spacetime of 5 or larger dimensions, matches the proposal for 5D wall domain Wilson fermions [11,64].…”
Section: Group Compactnessmentioning
confidence: 88%
See 2 more Smart Citations
“…The generation of the solitons relies on a 7D, but essentially 5D, space time matter induction and scattering from an embedded 7D flat or Einsteinian space [18,22,73,143]. These models are also inspired from non-multi-fold theories [19][20][21][23][24][25]. Handling of chiral fermions, absent in odd spacetime of 5 or larger dimensions, matches the proposal for 5D wall domain Wilson fermions [11,64].…”
Section: Group Compactnessmentioning
confidence: 88%
“…We have shown that SM and SM G is consistent on such a discrete spacetime. Note added on July 23, 2023: [184,185] further elaborates of consistency of QFT, Yang Mills and SM (as SMG) in the presence of gravity and seems to indicate that the universe must be multi-fold with a discrete spacetime and particles modeled as 7D space time matter induced or scattered QBall solitons or random walk patterns [18][19][20][21][22][23][24][25]119,153,165].…”
Section: Group Compactnessmentioning
confidence: 99%
See 1 more Smart Citation
“…In a multi-fold universe, the model of [1] recovers the positioning of the right-handed neutrino as living at the entry and exit points of the multi-folds, at the edge of spacetime, behind the massive Higgs boson [14,16,18]; and the particles encountered in the 7D space time matter induction and scattering model [17,29] (One of them was identified in [17] as potentially the resulting massive neutrino: the M* in [31]), with all the necessary caveats 4 . Interestingly, both Higgs and M* are seen, from the multi-fold spacetime, as at the edge and within the 7D (5D in [31]) embedding universe [17]. It could be the interpretation of doublet companions encountered in [1].…”
Section: Congruence Of Multi-fold Theories and The Multi-fold Gravity...mentioning
confidence: 99%
“…The particles mentioned in[17], as derived in[31], were examples, not endorsement of the model of[31], and so no claim that the approach indeed leads to the neutrino (tau) matching M*.…”
mentioning
confidence: 99%